Epidemiology, clinical manifestations, and laboratory findings of 1,590 human brucellosis cases in Ningxia, China - Liu, Bofei; Liu, Guangtian; Ma, Xueping; Wang, Fang; Zhang, Ruiqing; Zhou, Pan; Liu, Zhiguo; Li, Zhenjun; Jiang, Xuefeng (Frontiers in Microbiology, 2023)
Epidemiological and clinical analyses of brucellosis are vital for public health leaders to reinforce disease surveillance and case management strategies. In this study, we aimed to analyze the epidemiology and clinical features of 1590 cases of human brucellosis. Approximately 72.08% (1146) of the patients were male and 27.92% (444) were female. At least 88.18% (1402/1590) of the patients had a history of contact with sheep/goats and cattle, identified as the main risk factor for infection. The most common age group affected was 30–69 years, comprising 83.90% of all cases, with a median age of 47.3 years. Meanwhile, 75.03% (1193/1590) of the patients were farmers, followed by workers (10.50%, 167/1590). The spectrum of clinical manifestations varied; the major symptoms were fatigue (42.96%), joint pain (37.30%), and fever (23.33%). Arthritis was diagnosed in 989 patients, spondylitis in 469, and external genital complications were found in at least 53.96% (858/1590) of patients. In addition, approximately 41.25% (625/1515) and 24.53% (390/1590) of cases exhibited elevated CRP and D-dimer levels, respectively. Conversely, a significant decrease was observed in fibrinogen, total protein and albumin levels, affecting 48.36% (769/1590), 77.25% (1226/1586), and 91.80% (1456/1586) of patients, respectively. These data demonstrate that brucellosis is a severe wasting disease that leads to an imbalance in nutritional metabolism and a decline in immunity. The 86.70% (1379/1590) patients showed improvement with antibiotic therapy, while 13.27% (211/1590) patients experienced relapses or treatment failure. Brucellosis often presents with non-specific symptoms and laboratory findings, accompanied by multiple organ invaded, as well as being a vital challenge of diagnosis and treatment, so a high degree of suspicion is essential for a timely diagnosis and treatment. This study provides basic data and resources for developing tailored countermeasures to curb its further spread.